2021
DOI: 10.1080/21655979.2021.1984003
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast attenuates interleukin IL-1β-induced oxidative stress and apoptosis in chondrocytes by inhibiting CYSLTR1 (Cysteinyl Leukotriene Receptor 1) and activating KLF2 (Kruppel Like Factor 2)

Abstract: Montelukast attenuates interleukin IL-1β-induced oxidative stress and apoptosis in chondrocytes by inhibiting CYSLTR1 (Cysteinyl Leukotriene Receptor 1) and activating KLF2 (Kruppel Like Factor 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…TERTbutylhydroquinone can effectively prevent oxidative stress and inhibit apoptosis of rat chondrocytes by activating Nrf2 pathway (Yang et al, 2021). Li et al found that montelukast can effectively reduce oxidative stress and apoptosis in chondrocytes and improve the viability of chondrocytes (Li et al, 2021). Transforming growth factor β 1 can protect chondrocytes from oxidative stress by regulating autophagy (Kurakazu et al, 2021).…”
Section: How To Solve the Oxidative Stress In Knee Osteoarthritismentioning
confidence: 99%
“…TERTbutylhydroquinone can effectively prevent oxidative stress and inhibit apoptosis of rat chondrocytes by activating Nrf2 pathway (Yang et al, 2021). Li et al found that montelukast can effectively reduce oxidative stress and apoptosis in chondrocytes and improve the viability of chondrocytes (Li et al, 2021). Transforming growth factor β 1 can protect chondrocytes from oxidative stress by regulating autophagy (Kurakazu et al, 2021).…”
Section: How To Solve the Oxidative Stress In Knee Osteoarthritismentioning
confidence: 99%
“…TNF-α and IL-1β are key mediators of inflammatory activation and induction of oxidative stress in FLS and chondrocytes, leading to inflammatory factor secretion, FLS proliferation and invasion, and chondrocyte apoptosis. After confirming that the nanozyme effectively downregulated the secretion of TNF-α and IL-1β from activated macrophages, we explored whether it could also block the secretion of TNF-α and IL-1β from FLS and chondrocytes. For a start, we verified the uptake of MMV-MnO 2 @DSP in FLS and chondrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of KLF2 was enhanced in the process that montelukast attenuated chondrocyte apoptosis. 94 The role of KLF2 in this process was to reduce the proportion of chondrocyte apoptosis, decrease the expression of pro-apoptotic Bax, APAF-1, Cleaved caspase 3 and Cleaved PARP, and increase the expression of the anti-apoptosis protein B-cell lymphoma 2 (Bcl-2). 94 Similarly, Gao et al found that KLF2 overexpression significantly reduced the percentage of IL-1β-induced apoptosis in SW1353 cells.…”
Section: Klfs and Chondrocyte Apoptosismentioning
confidence: 99%
“…94 The role of KLF2 in this process was to reduce the proportion of chondrocyte apoptosis, decrease the expression of pro-apoptotic Bax, APAF-1, Cleaved caspase 3 and Cleaved PARP, and increase the expression of the anti-apoptosis protein B-cell lymphoma 2 (Bcl-2). 94 Similarly, Gao et al found that KLF2 overexpression significantly reduced the percentage of IL-1β-induced apoptosis in SW1353 cells. Mechanistically, KLF2 overexpression activates Nrf2/ARE signalling to promote the transcription of Nrf2 target genes, thereby inhibiting chondrocyte apoptosis.…”
Section: Klfs and Chondrocyte Apoptosismentioning
confidence: 99%
See 1 more Smart Citation